Sources of Work Stress of English Language Teachers in Secondary Government Schools in Saudi Arabia - Mohamad Ahmad Saleem Khasawneh (Newinera Publisher, 2021)
The study aimed to reveal the level of work stress among secondary school English language teachers in government schools affiliated with the education directorates in Abha, Saudi Arabia, and knowing the impact of both gender, and experience on their estimates. The study population consisted of (105) male and female teachers. A questionnaire was prepared to measure the level of work stress among teachers, and it consisted of (31) items. The results showed that the work pressures facing secondary school English language teachers were at a high level on the dimensions as a whole. The results also showed that there were no statistically significant differences due to the variable of gender and teaching experience.